The Effect of Plastic Pellet Substitution on Fine Aggregate and Gypsum Waste Substitution in Cement on the Compressive Strength of Lightweight Concrete - Muhammad Galuh Firdaus (Journal of World Conference (JWC), 2021)
Concrete is an important constituent material in a construction, concrete also has the constituent materials such as cement, aggregate, and water. However, the use of such compound materials can make an impact on health and environment, as cement production can produce CO2 emission gases, and the aggregate use resulting from mining activities can damage the environment in a long period of time. The experimental method, which is ways to reveal the causal relationship between two or more variables through careful experiments. These two forms are: exploratory experiments (aimed at the problem and hypothesis) and development experiments (aimed at proving hypotheses to make common generalizations.. Results of the test that has been conducted that strong press concrete on the 7th day with a strong result of the highest press obtained from a variation D of 9.76 MPa with a mixture of plastic seeds 0.6% and the waste of the 10%. Results of tests that have been conducted that strong press concrete on the 14th and 21st days with strong results of the highest press obtained at a variation of C amounted to 5.10 MPa on the 14th and 5.25 MPa on the 21st day with a mixture of 0.6% plastic seeds and a 5% waste of the range. The result of the test has been conducted that strong press concrete on the 28th day with a strong result of the highest press obtained from A Variation of 12.43 MPa with a mixture of 0.5% plastic seeds and a 5% of the waste of the. For the results of the overall variation that meets the quality of concrete with a target of K-125 on the 28th day of the variation A of 12.43 MPa, variation B of 10.60 MPa, C Variation of 11.32 MPa, D Variation of 10.21 MPa.